Evaluation of the tolerability and efficacy of a noncompetitive, reversible inhibitor of the α-amylase and α-glucosidase enzymes with a specific, standardized polyphenolic composition on the modulation of postprandial glycemic peaks in overweight patients - Cioni, Federico; Maioli, Claudio (Progress in Nutrition, 2018)
The prevalence of impaired fasting glucose (IFG) in the general population presents a significant clinical challenge given the high rate of progression to full-blown diabetes and the associated increase in cardiovascular risk and other complications, and justifies the need for early corrective intervention based on lifestyle changes supported by supplements to modulate postprandial glycemic peaks. This open-label study, based on a cross-over model, was conducted on a sample of 25 overweight patients with IFG taking part in a standardized lifestyle intervention program in order to analyze its effectiveness in modulating postprandial glycemic peaks as well as the gastrointestinal tolerability of a specific, standardized polyphenolic supplement (extracted from Ascophyllum nodosum and Fucus vesiculosus). The trend in capillary blood glucose values ​​measured in patients enrolled in the study confirms the ability of the product used to modulate glycemic fluctuations both after ordinary meals consumed in real-life conditions and after a standard meal with controlled intake of carbohydrates, compared to observed values after consuming the same meals without supplements. The homogeneity of the glycemic values ​​observed three hours after the standard meal, both with and without supplementation, also confirms the absence of late hypoglycemic effects.